LOCAL COMMUNITY PERCEPTION OF THE CHINESE TOURISTS BEHAVIOR IN BUNAKEN ISLAND, NORTH SULAWESI PROVINCE, INDONESIA - SAMBEKA, Vesty Like; WENAS, Pearl Loesye; SANGARI, Fonny; WEWENGKANG, Silvana Audry Rima; Towoliu, Benny Irwan (Revista de turism - studii și cercetări în turism, 2023)
The arrival of tourists from China to Indonesia has an impact on the country's foreign exchange, but there are also negative influences as reported by various world media that deplore the bad behavior of tourists from China. Many world mass media have published the bad behavior of them. In Manado itself there is no significant information about the bad behavior practiced by tourists from China. However, some information stated that bad behavior also occurred on Bunaken Island, but only local people on Bunaken Island know better because they interact with the them. This study aims to examine the assessment of local communities of the behavior of Chinese tourists on Bunaken Island, National Marine Park, North Sulawesi Province. The analytical method used is descriptive. The research instruments used are questionnaires, and Interview. Likert scale is used to categorize each question and use score interpretation to facilitate answers to respondents' assessments. The analysis used is descriptive through tables and percentages, as well as testing of the validity and reliability. The findings show that local people consider that Chinese tourists tend to be destructive and unfamiliar, so it gets attention from the tour manager to organize visitors who enter the tourist location.